Relevansi Pancasila Era Industry 4.0 dan Society 5.0 di Pendidikan Tinggi Vokasi - Raharja, Handy Yoga (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2019)
Pancasila is the basis of the Indonesian state which can be relevant in various scientific fields. Among other things in the field of information and technology which is currently developing rapidly coupled with the revolution of Industry 4.0 and Society 5.0. The revolution is closely related to technological development innovations, as well as the competence of Human Resources. So that Pancasila is very important to take part in improving human resource capabilities, especially in terms of soft skills.